2004
DOI: 10.1262/jrd.50.139
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimal Conditions for Parthenogenetic Activation and Subsequent Development of Rat Oocytes In Vitro

Abstract: Abstract. The present study was undertaken to determine optimal conditions for parthenogenetic activation and subsequent development of rat oocytes. Oocytes from immature Wistar-Imamichi (WI) and Sprague Dawley (SD) rats were activated by electrical stimulation in combination with 6-dimethylaminopurine (6-DMAP) to assess whether different rat strains display different responses to activation treatment. Since the cleavage rates of activated oocytes were significantly higher in WI than SD strain rats, WI rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 23 publications
(32 reference statements)
1
23
1
Order By: Relevance
“…Oocytes from the SD strain were more resistant to the strontium treatment than were those from the Wistar strain, and the overall activation efficiency was higher for SD oocytes [8]. However, when oocytes were electrically stimulated and then treated with 6-dimethylaminopurine, more activated oocytes from Wistar-Imamichi strain developed to the 2-cell and blastocyst stages than did those from the SD rats [9]. In addition, fertilized rat eggs of the SD outbred strain had a high capability of developing from the 1-cell to the blastocyst stage, whereas those of the SD inbred strains performed much more poorly [31].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Oocytes from the SD strain were more resistant to the strontium treatment than were those from the Wistar strain, and the overall activation efficiency was higher for SD oocytes [8]. However, when oocytes were electrically stimulated and then treated with 6-dimethylaminopurine, more activated oocytes from Wistar-Imamichi strain developed to the 2-cell and blastocyst stages than did those from the SD rats [9]. In addition, fertilized rat eggs of the SD outbred strain had a high capability of developing from the 1-cell to the blastocyst stage, whereas those of the SD inbred strains performed much more poorly [31].…”
Section: Discussionmentioning
confidence: 91%
“…It has been demonstrated that genetic background is an important determinant in the in vitro response of oocytes [7][8][9] and spermatozoa [10][11][12][13], as observed in different species, including mice and rats, as well as in different strains of the same species. These factors may be responsible for the different environmental requirements for successful IVF in different strains and species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 This suggested that the parameters for this culture condition needed to be altered to develop a successful long-term culture technique that could produce mature oocytes with the same potential as those matured in vivo. We hypothesized that if the oxygen tension in the incubator were decreased to in vivo levels for developing preantral follicles, the result would be an increase in the proportion of mature functioning oocytes obtained from the culture.…”
Section: Ambient Oxygen Culturementioning
confidence: 99%
“…However, increased space and cost requirements often limit the production of genetically modified rats in this manner [16]. Also, standard SCNT has proven to be very difficult to implement in the rat [17], [18], [19], [20], [21], [22], [23]. To date, only a single report [24] exists describing the successful generation of a rat by this method.…”
Section: Introductionmentioning
confidence: 99%